Reducing, reusing, and recycling in the furniture industry: A mini-review - Pralat, Barabara; Anna Owsian; Rogozinski, Tomasz (Talenta Publisher, 2024)
This study explores sustainable practices within the furniture industry, focusing on the principles of reduce, reuse, and recycle. Through a comprehensive review of scholarly literature retrieved from databases like Scopus, Web of Science, and Google Scholar a moderate corpus of articles is identified. The analysis reveals a predominant emphasis on strategies aimed at minimizing resource consumption, extending product lifespans, and optimizing material recovery. While reduce, reuse and recycle serve as foundational pillars of sustainable furniture production, the literature also highlights complementary principles such as